Pharmacogenetic warfarin dose refinements remain significantly influenced by genetic factors after one week of therapy - Horne, Benjamin D.; Lenzini, Petra A.; Wadelius, Mia; Jorgensen, Andrea L.; Kimmel, Stephen E.; Ridker, Paul M.; Eriksson, Niclas; Anderson, Jeffrey L.; Pirmohamed, Munir; Limdi, Nita A.; Pendleton, Robert C.; McMillin, Gwendolyn A.; Burmester, James K.; Kurnik, Daniel; Stein, C. Michael; Caldwell, Michael D.; Eby, Charles S.; Rane, Anders; Lindh, Jonatan D.; Shin, Jae-Gook; Kim, Ho-Sook; Angchaisuksiri, Pantep; Glynn, Robert J.; Kronquist, Kathryn E.; Carlquist, John F.; Grice, Gloria R.; Barrack, Robert L.; Li, Juan; Gage, Brian F. (Thrombosis and Haemostasis, 2012)
By guiding initial warfarin dose, pharmacogenetic (PGx) algorithms may improve the safety of warfarin initiation. However, once international normalised ratio (INR) response is known, the contribution of PGx to dose refinements is uncertain. This study sought to develop and validate clinical and PGx dosing algorithms for warfarin dose refinement on days 6–11 after therapy initiation. An international sample of 2,022 patients at 13 medical centres on three continents provided clinical, INR, and genetic data at treatment days 6–11 to predict therapeutic warfarin dose. Independent derivation and retrospective validation samples were composed by randomly dividing the population (80%/20%). Prior warfarin doses were weighted by their expected effect on S-warfarin concentrations using an exponential-decay pharmacokinetic model. The INR divided by that “effective” dose constituted a treatment response index. Treatment response index, age, amiodarone, body surface area, warfarin indication, and target INR were associated with dose in the derivation sample. A clinical algorithm based on these factors was remarkably accurate: in the retrospective validation cohort its R2 was 61.2% and median absolute error (MAE) was 5.0 mg/week. Accuracy and safety was confirmed in a prospective cohort (N=43). CYP2C9 variants and VKORC1–1639 G→A were significant dose predictors in both the derivation and validation samples. In the retrospective validation cohort, the PGx algorithm had: R2= 69.1% (p<0.05 vs. clinical algorithm), MAE= 4.7 mg/week. In conclusion, a pharmacogenetic warfarin dose-refinement algorithm based on clinical, INR, and genetic factors can explain at least 69.1% of therapeutic warfarin dose variability after about one week of therapy.
Keywords: Warfarin; VKORC1; CYP2C9; pharmacogenetic